PENERAPAN MEDIA POWER POINT UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF VOKAL BAGI ANAK TUNARUNGU (Single Subject Research di Kelas 1 SLB Luak Nan Bungsu Payakumbuh) - Yelsi - Anggraini (Jurnal Penelitian Pendidikan Khusus, 2012)
This research is backgrounded by deaf children who are not familiar with the vowels. This study aims to improve the ability to recognize all the vowels correctly and see if the props in power point can be applied to improve the ability to know the vowels. This research uses experimental research in the form of Single Subject Research (SSR) with AB designs. Subjects were child with hearing impairment X class 1 (one). Target behavior in this study is to know the child's ability to say the vowels and vowel indicates, is a form of assessment given percentage (%). The research was first seen from the baseline condition of the child's early ability in recognizing vowels. After that followed the intervention condition of the state continued to be treated. The data were processed by the graphics. So that the results of this study can be illustrated clearly. Having analyzed the data obtained the following results on the baseline phase the children only know one vowels, the letter [a]. In the intervention phase of learning is done by using media power point the child can recognize all vowels (value up to 100%). It means that learning with the use of media power point can be applied to improve the ability to know the vowels for children with hearing impairment. Researchers suggest that teachers and researchers in order to provide further learning by using media power point to recognize vowels in subsequent learning.